What is remembered & what is forgotten: shipwrecks and social memory on South Africa's Sunshine Coast - Dickson-Bow, Emma Jane (Rhodes University, Faculty of Humanities, Department of Anthropology)
Maritime heritage and its representation in South Africa, has been shaped by a settler colonial community heritage consciousness emphasising a heroic moral discourse legitimising local presence by settler communities. While much has been done to decolonise the representation of South African maritime heritage, at the local level small scale memorialisation continues to valorise maritime narratives that highlight the heroic aspects of historical settler colonial society, effectively concealing more fulsome of historical maritime events. Shipwrecks can function as potent tangible and intangible symbols of historical events, articulating a variety of perspectives on what constitutes social memory and history. This thesis examines the extension of public knowledge and representation of shipwreck maritime heritage on the Eastern Cape's coastal belt, known in tourist branding vernacular as the 'Sunshine Coast' (East London to Port Elizabeth). The case study of 'The Volo', a Norwegian barge wrecked near present day Kenton-on-Sea and Bushman's River Mouth (Boesmansriviermond) demonstrates how shipwreck narratives presented at the local public level can articulate a settler colonial community heritage consciousness that erases wider accounts of such stories. The reinterpretation and decentring of settler colonial maritime heritage stories allows for a more diverse and inclusive narrative that has the potential to promote social cohesion and social justice within restorative history work.
Keywords: Collective memory; Memorialization; Shipwrecks; Maritime heritage; Settler colonialism